Strength Theory Model of Unsaturated Soils with Suction Stress Concept. (10th November 2013) - Chen, Pan; Wei, Changfu; Liu, Jie; Ma, Tiantian
Abstract : A theoretical model is developed for describing the strength property of unsaturated soils. The model is able to predict conveniently the strength changes of unsaturated soils undergoing repeated changes of water content. Suction stress is adopted in the new model in order to get the sound form of effective stress for unsaturated soils. The shear strength of unsaturated soils is dependent on its soil-moisture state based on the results of shear experiments. Hence, the parameters of this model are related tightly to hydraulic properties of unsaturated soils and the strength parameters of saturated soils. The predictive curves by the new model are coincident with experimental data that underwent single drying and drying/wetting cycle paths. Hence, hysteretic effect in the strength analysis is necessary to be considered to predict the change of shear strength of unsaturated soils that underwent drying/wetting cycles. Once the new model is used to predict the change of shear strength, lots of time could be saved due to avoiding heavy and complicated strength tests of unsaturated soils. Especially, the model can be suitable to evaluate the shear strength change of unsaturated soils and the stability of slopes experienced the drying/wetting cycles.